A numerical study on thermal management of a lithium-ion battery module via forced-convective air cooling. (November 2021) - Singh, Lalan K.; Mishra, G.; Sharma, A.K.; Gupta, Anoop K.
Highlights: Air-cooled thermal management of battery module has been explored numerically. Thermal performance for inline and staggered cell arrangement was examined. Negligible effect of cell arrangement occurs beyond a critical number of cells. For small number of cells, the staggered arrangement slightly improves thermal uniformity. Abstract: Global environmental concerns over increased emissions from the transportation vehicles have driven research instincts towards development of clean energy vehicles. Pure and hybrid electric vehicles coupled with lithium-ion batteries for energy storage are environmental friendly options to realize the future dream of low carbon emissions. However, an efficient battery thermal management system (BTMS) is a prerequisite for safe operation of such high voltage batteries to avoid thermal runaway and degradation, thereby maintaining the temperature uniformity in the battery pack. Thus, the present work numerically investigates the performance of an air cooled battery module for efficient removal of heat generated during the discharge process at different values of air-flow velocity, cell configuration and the number of cells in the battery module. A coupled electrochemical-thermal model is employed to model the discharge behaviour of the battery in conjunction with the two-dimensional flow and heat transfer model to monitor the temperature in and out of each battery cell. A correlation is developed for the maximum temperature in the module as a function of the number of cells in the system. The flow configuration (inline or staggered arrangement) of cells in the stack is observed to have no influence over the velocity and thermal field beyond a critical value of number of cells in the module. Graphical abstract: Image, graphical abstract